The Social Essence Of The Problem Of Harassment And Violence Against Women In Families (Eurasian Journal of Learning and Academic Teaching, 2023)
The importance of studying the ways to prevent family violence in the world is related to the fact that this phenomenon affects the personal and social life of people and is a real obstacle to equality, social development and building a democratic society. Currently, gender equality is officially recognized as the single value unit of modern world development, as the principles of spreading the values of peace and tolerance, respecting human dignity, and refraining from violence. In world educational and scientific research centers, problems related to socio-psychological study of violence, especially violence against women, and giving the necessary suggestions and recommendations aimed at preventing violence through diagnostic research are being scientifically researched. Therefore, we can say that the development and progress of gender freedom will reach a high peak in the 21st century.